2011
DOI: 10.1139/w10-121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new fluorimetric DNA–DNA hybridization method

Abstract: Standardized procedures must be followed when characterizing, officially describing, and validly naming novel bacteria. For species descriptions, DNA-DNA hybridization still is needed for whole-genome comparisons between close relatives, but many established hybridization methods have drawbacks, such as requiring labeled or large amounts of DNA. We evaluated a new technique based on the spectrophotometric method in which renaturation rates are used for calculating the degree of binding, which estimates related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Urease was weakly positive after 6 days of incubation at 28 u C. Only a few carbon sources, mainly organic acids, could be used as sole sources of carbon. (99.6-99.8 %) show significant phenotypic and also genotypic differences sufficient for them to be classified as separate species, thus confirming the results of previous studies on bacteria of this genus (Kämpfer et al, 2006;Muller et al, 2006;Lang et al, 2007;Loveland-Curtze et al, 2009;Sahin et al, 2010). On the basis of these results as well as the phenotypic traits, we describe a novel species, for which the name Herminiimonas contaminans sp.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Urease was weakly positive after 6 days of incubation at 28 u C. Only a few carbon sources, mainly organic acids, could be used as sole sources of carbon. (99.6-99.8 %) show significant phenotypic and also genotypic differences sufficient for them to be classified as separate species, thus confirming the results of previous studies on bacteria of this genus (Kämpfer et al, 2006;Muller et al, 2006;Lang et al, 2007;Loveland-Curtze et al, 2009;Sahin et al, 2010). On the basis of these results as well as the phenotypic traits, we describe a novel species, for which the name Herminiimonas contaminans sp.…”
supporting
confidence: 90%
“…T was analysed as well because this trait was not included in the original description of this species (Loveland-Curtze et al, 2009) and it revealed a quinone system comprising Q-8 (94.1 %), Q-7 (5.4 %) and Q-9 (0.5 %). These quinone systems with Q-8 as the major compound were in agreement with the affiliation of the two strains to the class Betaproteobacteria and the description of the genus Herminiimonas (Fernandes et al, 2005) but high amounts of Q-7 clearly distinguished strain CCUG 53591 T from its close relative H. glaciei DSM 21140…”
mentioning
confidence: 99%
“…DNA-DNA hybridization was performed to analyse the relationships of the novel isolate with related taxa based on the thermal denaturation principles and equations [29,30] and by following a previously described optimized procedure [31]. For genomic characterization of strain Fur1 T , we performed DNA-DNA hybridization analyses between strain Fur1 T and the two reference strains, H. metalli KACC17381 T (97.5 %) and H. marinus KACC19042 T (97.1 %), using the fluorimetric method [32]. Hybridization was performed with five replications for each sample.…”
Section: Dna-dna Hybridizationmentioning
confidence: 99%
“…DNA-DNA hybridization was performed to determine the degree of genomic relatedness between strain W29 T and two closely related type strains, A. trabzonensis MS7 T and A. alkaliphilus AC-74 T , with >97 % 16S rRNA gene sequence similarity. DNA-DNA hybridization was performed by the fluorimetric method described by Loveland-Curtze (2011). The method combines spectrophotometric DNA reassociation kinetics as described by De Ley et al (1970) under consideration of the modifications described by Huß et al (1983).…”
mentioning
confidence: 99%